Urutan Kata, Fokus, dan Prosodi: Studi Lintas Bahasa pada Antarmuka Sintaksis - Prosodi Bahasa Indonesia dan Inggris - Rawuh Yuda Yuwana; Seli Marlina Radja Leba (Bhinneka: Jurnal Bintang Pendidikan dan Bahasa, 2026)
This study examines the interaction between word order, focus, and prosody in Indonesian and English within the framework of the syntax–prosody interface. While previous studies have largely focused on Indo-European languages, limited attention has been given to how these components interact in typologically distinct languages such as Indonesian. To address this gap, the study employs a mixed-method design combining corpus-based analysis and experimental approaches, including production and perception tasks. The corpus data reveal that English predominantly relies on prosodic marking to signal focus, whereas Indonesian demonstrates greater flexibility in word order, using syntactic fronting alongside prosodic cues. Experimental results further show that pitch (F0) is a stronger predictor of focus interpretation in English, whereas in Indonesian, a more distributed system involving both syntactic and prosodic features is observed. Statistical analyses, including linear mixed-effects models, confirm that language type, focus position, and prosodic parameters significantly influence focus interpretation. The findings contribute to the theoretical development of the syntax–prosody interface by demonstrating that focus realization is shaped by language-specific constraints while still reflecting universal principles of information structure. Methodologically, the study highlights the effectiveness of integrating corpus and experimental data in cross-linguistic research. These results provide new insights into typological variation in focus marking and offer a more comprehensive understanding of how syntax and prosody interact in natural language.